Research progress on recombinant NDV in cancer therapy - Sun, Jiating; Wang, Jia; Xiao, Min; Chen, Liming; Guan, Yi (Frontiers in Immunology, 2025)
Newcastle disease virus (NDV) has emerged as a promising oncolytic agent in cancer therapy. NDV not only directly lyses tumor cells but also activates the host’s innate and adaptive immune responses, demonstrating potent antitumor activity. However, the efficacy of wild-type NDV is often limited and inconsistent. Advances in genetic engineering have led to the development of a new generation of highly effective and safe recombinant Newcastle disease viruses (rNDVs) by deleting non-essential viral genes or incorporating exogenous functional genes. These genetically engineered NDVs further enhance antitumor activity and optimize the tumor microenvironment by increasing pro-inflammatory cytokine secretion and inducing systemic antitumor immunity. In this review, we summarize the current status of rNDVs, modification strategies, antitumor mechanisms, clinical applications, and combination therapies involving rNDVs. We also discuss the current challenges in utilizing NDV for cancer therapy, including determining the most effective delivery routes, developing strategies to evade neutralizing antibodies, overcoming tumor heterogeneity, and identifying relevant biomarkers.